PEMANFAATAN MEDIA KOMIK UNTUK MENINGKATKAN KEMAMPUAN MENULIS CERPEN SISWA KELAS X SMA NEGERI 2 KABANJAHE - AHMAD FADHLIN BATUBARA (Basastra, 2012)
Benefit Comic Media to Increase Ability Write Short Story Student In Grade X  State Senior High School 2 of Kabanjahe. The purpose of this study was to determine the Benefit  use of media comic to Increase Ability Write Short Story  in class X State Senior High School 2 of Kabanjahe. The population in this study is a whole class X  State Senior High School  2 of Kabanjahe consists of  7 classes. Samples taken in this study are 2 classes taken at random (random class), the class X-2 and X-4. Instrument or collection of data used to determine the ability Write Short Story students is to test directly. The test applied to posttest. From the analysis of the data it is known that there is a difference between the Comic Media And Conventional Technique to Write Short Story class X State Senior High School  2 of  Kabanjahe. Calculation results obtained by t-test to more than TTable is 5.78> 2.02 at the 5% significance level. The calculation nil hypothesis test (Ho) is rejected and the alternative hypothesis (Ha) is accepted. It proves that learning to Write Short Story using  Comic Media is more effective than the Conventional Technique.   keyword, Write Short Story, Comic Media.